Un port sans rivage ? Grand commerce, réseaux et personnalités marchandes à Perpignan à la fin du Moyen Âge - Coulon, Damien (Bibliothèque de la Casa de Velázquez, 2023)
This book reconstructs Perpignan's economic activities and the merchant networks, particularly foreign ones, that deployed them across the Mediterranean between the end of the 13th century and the end of the 15th century. Thanks to a wealth of handwritten correspondence, it also traces the career and profile of the city's leading businessman at the turn of the 15th century, the origin of an influential lineage. It thus reconstructs a little-known part of the city's history.